Differential Pulse Voltammetric Tuning of the Screen-Printed Carbon Electrode Surface to Enhance the Electrochemical Performance and Multiplex Detection - Mamun M.A.; Wahab Y.A.; Hossain M.A.M.; Hashem A.; Hamizi N.A.; Chowdhury Z.Z.; Muhamad Hattad S.F.W.; Badruddin I.A.; Kamangar S.; Johan M.R. (Institute of Physics, 2024)
Screen-Printed Carbon Electrode (SPCE) has shown tremendous scope for the miniaturization and commercialization of low-cost electrochemical sensors and biosensors devices. But the commercial SPCEs have a narrow potential window (PW) that limits their versatile applications for various analytes owing to the presence of some inherent redox peaks in the wider PW. In this work, we have explored the most effective and innovative electrochemical tuning of the SPCE surface using DPV (differential pulse voltammetry) for the removal of those inherent redox peaks that are responsible for narrowing the working PW. After that, the electrochemical performance of the tuned SPCE electrode was evaluated in terms of a range of electrochemical parameters including reproducibility by CV (Cyclic Voltammetry), DPV and EIS (electrochemical impedance spectroscopy) measurements using [Fe(CN)6]3?/4? as a model redox analyte. In addition, the suitability of the tuned electrode for multiple analytes detection was tested in presence of a mixture of Cd2+ (cadmium), Cu2+ (copper) and Hg2+ (Mercury) ions using CV and DPV techniques. The electrochemical analysis data show that after electrochemical DPV treatment, the SPCE surface exhibits excellent reproducibility and electrochemical performance within a wider PW minimizing their inherent drawback creating a wide scope of their precise applications in various fields. 2023 The Electrochemical Society (ECS). Published on behalf of ECS by IOP Publishing Limited.